SUPERVISORS PERFORMANCE OF BASIC SCHOOL IN THE TIME OF COVID-19 IN SUBANG - Fitria Zulfa (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The Covid-19 virus outbreak has had a significant impact on various aspects of life. For the world of education, this impact occurs in the aspect of educational supervision as happened to the performance of supervision in the Subang sub-district, Subang district. The study aims to describe the performance of supervisors during the Covid-19 period and its impact on the quality of Islamic education learning in elementary schools in Subang district. The type of research used is qualitative with a case study approach. The data was collected by means of observation, interview, literature study, and documentation techniques. The results showed that the performance of primary school supervisors in Subang district during the Pandemic was carried out through a remote surveillance system namely by using Whatsapp Groups. Supervision activities carried out include coaching, making LKH reports, RKB, Home Study Activity Reports, and Assessment of Employee Performance Targets. Even though the Whatsapp Group media has a number of deficiencies in its application to the remote surveillance system, in the midst of a pandemic, education supervision in the elementary school environment of the Subang sub-district continues, because after all the education process in Indonesia must run optimally.